2020
DOI: 10.3390/ijerph17062049
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Private Health Insurance on Universal Health Coverage Objectives in China: A Systematic Literature Review

Abstract: Background: We conducted a systematic review on the role of private health insurance to complement the social health insurance system towards achieving universal health coverage in China. This review presents the impacts of private health insurance on expanding coverage, increasing access to healthcare, and financial protection. Methods: A systematic review was conducted by searching peer-reviewed articles published between January 2000 and March 2018 in Web of Science, PubMed, and China Knowledge Resource Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…In China, government encouragement of the expansion of PHI is not for the purpose of covering individuals who are unable to acquire SBMI. Rather, PHI in China is a form of supplementary coverage for individuals who are already enrolled in the SBMI scheme [8]. Our study revealed that PHI purchasing was significantly associated with household financial status, including household income and medical spending.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In China, government encouragement of the expansion of PHI is not for the purpose of covering individuals who are unable to acquire SBMI. Rather, PHI in China is a form of supplementary coverage for individuals who are already enrolled in the SBMI scheme [8]. Our study revealed that PHI purchasing was significantly associated with household financial status, including household income and medical spending.…”
Section: Discussionmentioning
confidence: 68%
“…Private health insurance (PHI) was initially introduced in China in the 1980s [8], and it helped to expand the breadth of universal health coverage (UHC) in the absence of SBMI. With the rapid increase in income in the last 20 years, individuals now seek enhancements to the quality of healthcare [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such types of research are program design, implementation, evaluations, related policies, strategies, activities, etc. [13][14][15] Last but not least, SR must be used by creative model other than narrow and classical way so that coming researcher shall develop and improve with more pragmatic approaches.…”
mentioning
confidence: 99%
“…This explains the growing private healthcare plan market in China, and the state-led maternity insurance fund managers can learn from them. Suffice to say that such an ambitious venture may come at a cost, but this can be controlled [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of maternity insurance in China has been decentralized; hence the day-to-day decision-making starts at the local community, county, provincial or regional government before it is approved at the national level [ 22 ]. As is with every form of insurance scheme, the maternity insurance scheme in China comprises of an inlet or inflow sources (income) and the outlet or outflow channels which are the expenditure component [ 23 ]. In most provinces in China, four main sources of funds flow into the maternity insurance fund.…”
Section: Introductionmentioning
confidence: 99%